Optimization of ultrasound-assisted extraction of bioactive compounds from Caryocar brasiliense (Research, Society and Development, 2021)
Caryocar brasiliense, popularly known as pequi, is a species that has a high content of phenolic compounds with biological activities. In this work, the ultrasound-assisted extraction process of bioactive compounds of the pequi leaves was optimized with Box-Behnken factorial design. Four independent variables were investigated: sample concentration (liquid-solid ratio, LS), ethanol concentration (EtOH/H2O % v/v), UAE time (ultrasound-assisted extraction) and UAE temperature. The Response Surface methodology was used to point out the most important variable in the process. The results revealed the EtOH/H2O (% v/v) the most significant effect on the extraction of phenolic compounds. The optimum condition for extraction was an ethanol concentration of 60 %, UAE time of 30 min, a UAE temperature of 42 °C, and LS 18.7: 1. Under these conditions 6.30 mg GAE/g DW (n = 3) were extracted (mg gallic acid equivalent /g of dry weight). The observed experimental results confirm the suitability of the model used and its success for the optimization of extraction conditions.